Integration concepts and praxis in Slovenia - Lazarević, Žarko (The Development of European and Regional Integration Theories in Central European Countries, 2022)
The chapter deals with the political, economic, and social integration strategies and practices of the modern period that were developed to integrate the Slovene ethnic territory. The concepts discussed represent the different political realities in the periods of the Habsburg monarchy, Yugoslavia, and the independent state. The concept of ʻUnited Slovenia’ formed the basis of national ideology in the first period. Toward the end of the 19th century, the idea of ʻUnited Slovenia’ was combined with the idea of Yugoslavism. The goal was to increase the relative importance of Slovenes and improve the chances of realizing the maximalist goal of the national ideology. The 20th century was marked by communist authorities during the second part of the 20th century, a new concept unite the ethnic area on a cultural level, regardless of state borders. In the late 1980s, during a profound political, economic, and social crisis, a new integration concept emerged that aimed at full statehood for Slovenia and integration of the ethnic territory through incorporation into the European Union. KEYWORDS: Slovenia, Yugoslavia, Habsburg monarchy, national ideology, national movement, integration concepts